\\\\\\\\\\\\\\\ 𝑃(𝑡1 ) = log 𝑎 (𝑡1 ) + 𝑏 𝑃(𝑡2 ) = 𝑐 × 𝑠𝑖𝑛(𝑑(𝑡2 − 𝑓)) + 𝑔 𝑃(𝑡1 ) = ℎ × 𝑒 𝑘𝑡1 + 𝑝 𝑃(𝑡2 ) = 𝑙 1 + 𝑚 × 𝑒 −𝑛𝑡2 𝑃(𝑡1 ) = log 𝑎 (𝑡1 ) + (−5.8073 × 109 ) 𝑃(𝑡2 ) = (−3.9728148011 × 1014 ) × 𝑠𝑖𝑛(0.0000412242(𝑡2 − (−36279.8))) + (3.9728177204 × 1014 ) 𝑃(𝑡1 ) = (−2.5618 × 1021 ) × 𝑒 −0.0162912𝑡1 + (5.251 × 107 ) 𝑃(𝑡2 ) = (1.3671 × 1011 ) 1 + (3.894 × 1012 ) × 𝑒 −(0.0129318)𝑡2 𝑑 1 =− 𝑑𝑡 𝑡 ln 0.999999998699 𝑑 = −8732522286 × 𝑐𝑜𝑠 (0.0000412242(𝑡 + 36279.8)) 𝑑𝑡 −16377591400.19999\𝑐𝑜𝑠 (0.0000412242(𝑥 + 36279.8)) 𝑑 = (4.17348 × 1019 ) × 𝑒 {−0.0162912𝑡} 𝑑𝑡 𝑑 6.88423 × 1021 𝑒 −0.0129318𝑡 = 𝑑𝑡 (1 + 3894000000000𝑒 −0.0129318𝑡 )2 𝑑/𝑑𝑡 = −1/(𝑡 ln 0.999999998699 ) 𝑑/𝑑𝑡 = −8732522286 × 𝑐𝑜𝑠 (0.0000412242(𝑡 + 36279.8)) 𝑑/𝑑𝑡 = (4.17348 × 10^19) × 𝑒^(−0.0162912𝑡) 𝑑/𝑑𝑡 = (6.88423 × 10^21 𝑒^(−0.0129318𝑡))/(1 + 3894000000000𝑒^(−0.0129318𝑡))^2